2022
DOI: 10.1126/sciimmunol.abp9312
|View full text |Cite
|
Sign up to set email alerts
|

An ACE2-blocking antibody confers broad neutralization and protection against Omicron and other SARS-CoV-2 variants of concern

Abstract: The ongoing evolution of SARS-CoV-2 has resulted in the emergence of Omicron, which displays striking immune escape potential through mutations at key antigenic sites on the spike protein. Many of these mutations localize to the spike protein ACE2 receptor-binding domain, annulling the neutralizing activity of therapeutic antibodies that were effective against other Variants of Concern (VOCs) earlier in the pandemic. Here, we identified a receptor-blocking human monoclonal antibody, 87G7, that retained potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 85 publications
(165 reference statements)
6
52
0
Order By: Relevance
“…The stability peaks for the interacting antibodies A23-58.1 (Figure 5B) and B1-182.1 (Figure 5D) corresponded to the heavy chain positions T30, S31, and S32 interacting with F456 on the RBD, and the heavy chain residues 90-95 forming contacts with the F486 position of the RBD. Our findings agree with the structural analysis of the most potent antibodies against Omicron sublineages BA.1 and BA.2, showing that their high binding affinity and neutralizing activity are driven by targeting this very group of conserved and RBD stability-essential sites [113][114][115].…”
Section: Simulations and Distance Fluctuation Analysis Of Conformatio...supporting
confidence: 90%
See 1 more Smart Citation
“…The stability peaks for the interacting antibodies A23-58.1 (Figure 5B) and B1-182.1 (Figure 5D) corresponded to the heavy chain positions T30, S31, and S32 interacting with F456 on the RBD, and the heavy chain residues 90-95 forming contacts with the F486 position of the RBD. Our findings agree with the structural analysis of the most potent antibodies against Omicron sublineages BA.1 and BA.2, showing that their high binding affinity and neutralizing activity are driven by targeting this very group of conserved and RBD stability-essential sites [113][114][115].…”
Section: Simulations and Distance Fluctuation Analysis Of Conformatio...supporting
confidence: 90%
“…The stability peaks for the interacting antibodies A23-58.1 (Figure 5B) and B1-182.1 (Figure 5D) corresponded to the heavy chain positions T30, S31, and S32 interacting with F456 on the RBD, and the heavy chain residues 90-95 forming contacts with the F486 position of the RBD. Our findings agree with the structural analysis of the most potent antibodies against Omicron sublineages BA.1 and BA.2, showing that their high binding affinity and neutralizing activity are driven by targeting this very group of conserved and RBD stability-essential sites [113][114][115]. Structural map of the distribution peaks along with the Omicron positions (Figure 5E,F) illustrated the preferential localization of the stability centers in the RBD core and the immobilized region of the binding interface, while Omicron sites are located in the more flexible RBD regions.…”
Section: Simulations and Distance Fluctuation Analysis Of Conformatio...supporting
confidence: 90%
“…While this selected hybridoma clone was effective against the virulent Delta strain, it did not effectively neutralize the Omicron pseudovirus (Supplementary Figure 2 B). We have also evaluated he Regeneron monoclonal antibodies REGN10933 (Casirivamab) and REGN10987 (Imdevi-mab), the Eli Lilly cocktail [consisting of LY-CoV555 (Bamlanivimab) and LY-CoV016 (Etesevimab)], as well as RBD mAb-1 and RBD mAb-3 for the ability to neutralize SARS-CoV-2 variants of concern ( Table 1 ) ( Hwang et al, 2022 , Du et al, 2022 , Lusvarghi et al, 2022 ). REGN10933 (Casirivamab) potently neutralized Alpha and Delta, but had no detectable activity against Beta, Gamma and Omicron.…”
Section: Resultsmentioning
confidence: 99%
“…The cryo-EM structure revealed that 87G7 binds the ACE2 receptor binding site by targeting a patch of hydrophobic residues Y421, L455, F456, F486 and Y489 that are highly conserved among SARS-CoV-2 variants and where mutations occur at extremely low frequency (< 0.05%) of human-derived SARS-CoV-2 sequences. A considerable number of residues that are mutated in SARS-CoV-2 variants, including K417N, L452R, S477N, T478K, E484A, E484K, F490S, Q493R are close to the 87G7 core epitope but are unable to elicit mutational escape [57]. Biochemical and functional studies isolated 323 human monoclonal antibodies and showed that a subset of 24 out of 163 RBD-recognizing antibodies potently neutralized all SARS-CoV-2 variants of concern, including Omicron [58].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the ternary complex of the Omicron complex with a combination of B1-182.1 and A19-46.1 antibodies targeting different binding epitopes and trapping 3 RBD-up S conformation suggested a mechanism of the observed synergistic increase in neutralization potency compared with that of the individual antibodies [56]. A recent study identified a neutralizing human monoclonal antibody 87G7 with a broad-spectrum neutralization efficacy achieved via ACE2 binding inhibition mechanism and showing robust neutralizing activity against multiple VOC’s including the Omicron variants [57]. The cryo-EM structure revealed that 87G7 binds the ACE2 receptor binding site by targeting a patch of hydrophobic residues Y421, L455, F456, F486 and Y489 that are highly conserved among SARS-CoV-2 variants and where mutations occur at extremely low frequency (< 0.05%) of human-derived SARS-CoV-2 sequences.…”
Section: Introductionmentioning
confidence: 99%